The synergic effect of polyethylene fibres and CNT on the properties of ultralightweight cementitious composites - Huiyuan Liu; Mohamed Elchalakani; Sherif Yehia; Yee-Kwong Leong; Peng Du (Developments in the Built Environment, 2023)
This paper presents an experimental investigation utilizing ordinary Portland cement (OPC), carbon nanotube (CNT), metakaolin (MK) and 1.75% polyethylene (PE) fibres to develop a high performance CNT and fibre-reinforced ultra-lightweight cementitious composites (ULCC). Ultra-low density was achieved by using cenospheres. The effects of different dosages of CNT, different types of binders and PE fibres were investigated. The workability, hardened properties (density, compressive strength and flexural strength), sorptivity, microstructure and cost of each mix were also investigated. From this experiment, PE and CNT-reinforced high-strength ULCC with a dry density of around 1500 kg/m3, compressive strength of around 87 MPa and flexural strength of around 18 MPa with flexural hardening can be produced. The effect of CNT and the synergic effect of CNT and PE fibres were investigated and discussed. The synergic effect of CNT was better than the combination of the separate effects of CNT and PE fibres. Compared to the reference mix MRF, when combined with 1.75% PE fibres, 0.2%, 0.4%, 0.6% CNT can improve 260%, 276% and 239% of flexural strength, increase by 35.6%, 61% and 58.5% of compressive strength, 4.5%, 29% and 21.3% for specific strength. It was found that the cost of each mix increases by around 1067 AUD per cubic meter by the increase of 0.2% CNT in each mix. Finally, from multi-criteria analysis, M0.4CNTPE was recommended in this study.